2015
DOI: 10.3389/fmicb.2015.01253
|View full text |Cite
|
Sign up to set email alerts
|

On the Ancestral UDP-Glucose Pyrophosphorylase Activity of GalF from Escherichia coli

Abstract: In bacteria, UDP-glucose is a central intermediate in carbohydrate metabolism. The enzyme responsible for its synthesis is encoded by the galU gene and its deletion generates cells unable to ferment galactose. In some bacteria, there is a second gene, galF, encoding for a protein with high sequence identity to GalU. However, the role of GalF has been contradictory regarding its catalytic capability and not well understood. In this work we show that GalF derives from a catalytic (UDP-glucose pyrophosphorylase) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 78 publications
(133 reference statements)
2
21
0
Order By: Relevance
“…Consistent with results from previous studies, the first gene in all cps clusters was galF ( Ebrecht et al 2015 ) followed by a putative glucose phosphatase ( cpsACP ), the JUMPstart sequence (‘just upstream of many polysaccharide starts’) followed by the translocation and surface assembly genes ( wzi, wza, wzb and wzc ) ( Rahn et al , 1999 ). Although the genes responsible for transport into the periplasm and polymerization ( wzx and wzy ), UndPP-linkage ( wbaP or wcaJ ) and a 6-phosphogluconate dehydrogenase [ gnd , a housekeeping gene not required for CPS synthesis ( Chen et al 2010 )] were universally present, they were not found at fixed locations in these clusters.…”
Section: Resultssupporting
confidence: 89%
“…Consistent with results from previous studies, the first gene in all cps clusters was galF ( Ebrecht et al 2015 ) followed by a putative glucose phosphatase ( cpsACP ), the JUMPstart sequence (‘just upstream of many polysaccharide starts’) followed by the translocation and surface assembly genes ( wzi, wza, wzb and wzc ) ( Rahn et al , 1999 ). Although the genes responsible for transport into the periplasm and polymerization ( wzx and wzy ), UndPP-linkage ( wbaP or wcaJ ) and a 6-phosphogluconate dehydrogenase [ gnd , a housekeeping gene not required for CPS synthesis ( Chen et al 2010 )] were universally present, they were not found at fixed locations in these clusters.…”
Section: Resultssupporting
confidence: 89%
“…The ADP-Glc PPase from R. jostii was characterized as a homotetrameric protein exhibiting similar S 0.5 values for substrates to those calculated for the enzyme from M. tuberculosis , but fivefold higher than those from the S. coelicolor enzyme, although with levels of activity in the same order of magnitude than the latter. Comparatively, the catalytic efficiency of the ADP-Glc PPase from R. jostii exhibits the lowest values with respect to homologous proteins from S. coelicolor and M. tuberculosis or even other PPases so far characterized ( Iglesias et al, 1991 ; Charng et al, 1992 ; Ballicora et al, 1995 , 2002 ; Ugalde et al, 1998 ; Uttaro et al, 1998 ; Gomez-Casati and Iglesias, 2002 ; Bosco et al, 2009 ; Asencion Diez et al, 2012 , 2013a , b , 2014 , 2015 ; Machtey et al, 2012 ; Ebrecht et al, 2015a , b ). Thus, the R. jostii ADP-Glc PPase might be an enzyme with low basal activity, as proposed for the ADP-Glc PPase from Streptococcus mutans with homotetrameric conformation (GlgC, with similar values of catalytic efficiency; Asencion Diez et al, 2013a ).…”
Section: Discussionmentioning
confidence: 91%
“…All other chemicals were of the highest quality available. Recombinant ADP-Glc and UDP-Glc pyrophosphorylases from Escherichia coli were expressed in E. coli and purified to near homogeneity as previously described ( Ballicora et al , 2002 ; Ebrecht et al , 2015 ).…”
Section: Methodsmentioning
confidence: 99%